The Role of Molecular Biology and Biotechnology in Enhancing Pathology Analysis for Cancer Research and Treatment - Kazem, Baneen Abbas’s Hussain; Amin, Salsbel Slahaldin M.; Salah, Aesha Dler Muhamad; Hunoosh, Athraa Badeaa (American Journal of Biology and Natural Sciences, 2025)
Molecular biology—the study of living organisms at the cellular level—and biotechnology—the application of biological systems to technological innovation—remain pivotal in unraveling the ever-expanding genetic framework of cancer. These disciplines parallel the growth of data science, empowering scientific progress and enabling a multidisciplinary understanding of malignancy in the postgenomic era. The application of molecular biology and biotechnology has already elucidated fundamental aspects of cancer biology and has begun to revolutionize prevention, detection, and treatment strategies. The pathology department plays a critical role in the preanalytical phase of molecular analyses, an essential step toward delivering personalized treatment and developing innovative therapies. The success of contemporary molecular and proteomic techniques largely depends on the quality of biological material, which may be derived from fresh or formalin-fixed, paraffin-embedded (FFPE) tissues. Consequently, tissue fixation and preservation undergo a rigorously standardized preparation process. Enhancements in preanalytical standardization and quality control have markedly reduced the rate of error associated with molecular tests. Molecular biology continues to provide an extensive repository of information pertinent to cancer, much of which continues to transform clinical oncology and treatment protocols.